The Representation Of Lgbt In Disney Films (Semiotic Analysis In The Films Strange World And Lightyear) - Azizah Nur Aulia; Abdul Firman Ashaf; Tina Kartika; Nanang Trenggono (Journal of World Science, 2025)
Disney, as a production house and global film publisher, now appears to be heavily emphasizing woke culture values, one of which includes advocating for LGBT minorities through messages in its films. LGBT as an agenda in the woke culture movement is presented by the media in their respective styles and for example, the LGBT form of film media appears on the side actors who are gay, lesbian, bisex, transgender to queer who are present in the scope of life of the main actor of the film. This research aims to analyze and explain how Disney represents LGBT behavior in the context of film media The method used by the researcher is a literature study conducted by collecting data in the form of documents consisting of scene images and dialogue in films. During the data analysis process of the research, the author utilized Christian Metz' semiotics method to interpret the cinematic elements of the film and extract the meaning of messages in each scene Furthermore, this study is supported by the theory of multiculturalism in politics. The results obtained by the researcher are that in the film Strange Word (2022), Ethan, who is the main character, is gay and he loves his male friend named Diazo Furthermore, in the film Lightyear (2022), Commander Hawthorne is the main character's friend, Buzz Lightyear, and she is a lesbian.